Invasive pneumococcal disease in patients with haematological malignancies before routine use of conjugate vaccines in Finland. Issue 5 (3rd May 2016) - Lindström, Vesa; Aittoniemi, Janne; Lyytikäinen, Outi; Klemets, Peter; Ollgren, Jukka; Silvennoinen, Raija; Nuorti, J. Pekka; Sinisalo, Marjatta
Abstract: The baseline national invasive pneumococcal disease (IPD) incidence rate, serotype distribution and serotype coverage of pneumococcal vaccines were evaluated in patients with Hodgkin's and non-Hodgkin's lymphomas, myeloma and leukaemia within 1 year after haematological diagnosis during 1995–2002, before introduction of pneumococcal conjugate vaccines. Pneumococcal serotype distribution among these patients was different from serotypes causing IPD in the general population. The serotype coverages of PCV13 and PPSV23 were 57% and 64%, respectively, lower than in the general population. This reflects a higher predisposition to IPD in vaccinated patients with haematological malignancies and possibly less benefit of herd immunity gained with the wide use of pneumococcal conjugate vaccines in the general population. This data will be useful as a baseline for determining the future role of adult PCV vaccination in these patient groups.